2015
DOI: 10.1103/physrevb.92.201103
|View full text |Cite
|
Sign up to set email alerts
|

Charge ordering geometries in uniaxially strainedNbSe2

Abstract: Recent STM experiments reveal niobium diselenide to support domains of striped (1Q) charge order side-by-side with its better-known triangular (3Q) phase, suggesting that small variations in local strain may induce a quantum phase transition between the two. We use a theoretical model of the charge order in NbSe2, based on a strong momentum-and orbital-dependent electron-phonon coupling, to study the effect of uniaxial strain. We find that as little as 0.1% anisotropic shift in phonon energies breaks the three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
5
23
1
Order By: Relevance
“…The transition we see at 20 K could be the turning-on of these fluctuations. A sharp turn-on of CDW fluctuations has previously been proposed to account for a resistivity bump in the q2D transition metal oxide bronze P 4 W 10 O 38 [31,32] and has been predicted in the q2D transition metal dichalcogenide NbSe 2 [23,33]. Despite the fluctuating CDW order being along the b-direction chains it would not necessarily give a strong resistivity boost in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…The transition we see at 20 K could be the turning-on of these fluctuations. A sharp turn-on of CDW fluctuations has previously been proposed to account for a resistivity bump in the q2D transition metal oxide bronze P 4 W 10 O 38 [31,32] and has been predicted in the q2D transition metal dichalcogenide NbSe 2 [23,33]. Despite the fluctuating CDW order being along the b-direction chains it would not necessarily give a strong resistivity boost in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the 1Q regions may be stabilized by local strain on the sample's surface. The fact that both 1Q and 3Q order can be observed sideby-side on the same sample suggests that the 3Q order is in fact close to a quantum critical point, and can be destroyed by relatively little strain 14,16 . To quantify this hypothesis, we now compare the free energy of the 3Q ordered state to that of the single Q pattern, as a function of externally-applied uniaxial strain.…”
Section: Uniaxial Strainmentioning
confidence: 96%
“…Following the minima of the renormalized phonon dispersions in Fig. 21 as a function of temperature, gives an indication of the expected thermal evolution of the CDW vector Q CDW characterizing the local order in the fluctuating islands of the pseudogap phase 16 . The regions of stability surrounding defects are expected to grow continuously as temperature decreases, until at T CDW they overlap sufficiently for separate regions to become correlated.…”
Section: The Cdw Pseudogapmentioning
confidence: 98%
See 2 more Smart Citations